Soft Luxury dalam Branding Produk Lokal: Analisis Etnografi Visual Instagram ESQA Cosmetics - Kevin Wijaya Sugiarto; Ririn Puspita Tutiasri (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The growth of the local cosmetics industry in Indonesia has encouraged brands to build strong visual identities through social media platforms. One of the concepts increasingly applied in visual communication is soft luxury, which represents luxury through subtle expressions characterized by minimalist, elegant aesthetics that are closely connected to everyday life. This study aims to analyze how the meaning of soft luxury is constructed through visual representation practices and audience interactions on ESQA Cosmetics’ Instagram posts. This research employs a qualitative method with a visual ethnography approach. Data were collected through non-participant observation of posts on the official Instagram account @esqacosmetics, visual documentation in the form of screenshots, and relevant literature studies. The data were analyzed using a descriptive-interpretative approach through data reduction, data presentation, and conclusion drawing. The results show that the representation of soft luxury is consistently constructed through the use of neutral color palettes such as nude, beige, cream, and rose gold, minimalist visual compositions, soft lighting, elegant product packaging, and representations of modern women with natural gestures and simple makeup styles. The meaning of soft luxury is not only shaped by ESQA Cosmetics’ visual communication strategies but also through the process of audience interpretation and interaction on Instagram. This study demonstrates that brand identity on social media is a social construction formed through the relationship between visual representation and audience experiences within the digital cultural space.